Innovations of Integrated Islamic Education in Indonesia and Brunei Darussalam: Trends, Challenges, and Opportunities - Ely Fitriani; Evi Fatimatur Rusydiyah; Siti Amaliati; Nurisan Doloh; Fareesah Koowa (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
Integrated Islamic education has become an integral part of efforts to innovate in religious education that aligns with the progress of the times. This study presents a systematic literature review on educational innovation through integrated Islamic education. The method employed in this research is Systematic Literature Review (SLR), utilizing the PRISMA protocol with its stages, including identification, screening, eligibility, inclusion, abstraction, and data analysis. The process is assisted by the applications Publish or Perish, Zotero, and the PRISMA Flow Diagram on the web. The research findings indicate that the distribution of studies on integrated Islamic education in Indonesia amounts to 21 articles, while in Brunei Darussalam, there are 3 articles. As for integrated Islamic education in Indonesia, it can be observed in the form of improvisation of learning models, internalization of Islamic values in general content, curriculum redesign, and student activity management. Meanwhile, in Brunei Darussalam, the Malay Islamic Monarchy (MIB) concept is employed, and this concept has led to the implementation of the SPN-21 curriculum policy, which aims to create individuals who are faithful, pious, morally upright, and proficient in technology.